The Steroidal Glycoalkaloids from Solanaceae: Toxic Effect, Antitumour Activity and Mechanism of Action - Sucha, Lenka; Tomsik, Pavel (Planta medica, 2016)
Steroidal glycoalkaloids present in Solanaceae are toxic compounds biosynthesised for the protection of the plants. However, many health benefits of these compounds have been reported so far. One of their promising targets might be cancer, as demonstrated in a large number of studies. However, the main mechanism of action seems to be unclear. It could include the induction of apoptosis or trigger a necrosis with a subsequent inflammatory response. The relatively high systemic toxicity of steroidal compounds is another effect that must be taken into account in anticancer research. The main aim of this work was to summarise the recent progress in the investigation of the mechanisms of their antitumour action and to discuss their potential.
Keywords: Antineoplastic Agents, Phytogenic; Solanaceae; zvířata; Humans; fytogenní protinádorové látky; Plant Extracts; Solanaceous Alkaloids; rostlinné extrakty; alkaloidy Solanaceí; lidé; Animals